Democracia cooperativa / J.P. Warbasse ; traducción de Jacobo Prince, Miguel Ángel Angueira y Silvia M. Angueira - Prince, JacoboAngueira Miranda, Miguel ÁngelAngueira, Silvia M.; Warbasse, James Peter (Biblioteca de cultura social. Sección VIII, Ensayos e interpretaciones)
Bibliografía: p. 365-367